"Part of me feels like there must be something missing": a phenomenological exploration of practising psychotherapy as a clinical psychologist. Issue 2 (4th March 2018) - McMahon, Aisling
ABSTRACT: The experience of practising psychotherapy as a clinical psychologist was explored through a small number of in-depth interviews. Using Interpretative Phenomenological Analysis, three main themes were identified: "Feeling there's something missing", "Being able to get in there emotionally" and "Needing somewhere to go for support". This study suggests that training for psychotherapy work can be experienced as piecemeal and fragmented, contributing to professional self-doubt, with clinical psychologists seeking more structured, cohesive training in this area. It also suggests that engagement in personal therapy can contribute to greater emotional capacity as a psychotherapy practitioner, although clinical psychologists can fear engaging in something that is unfamiliar. In addition, the psychologists highlighted the felt necessity of safe and satisfying supervision for resilient practice.